Pertumbuhan Enterococcus faecalis ID 6017 dan Kemampuan Dekolorisasi Beberapa Konsentrasi Orange II dalam Sistem Sinambung - Kara, Patrisia Ilene; Meitiniarti, V. Irene; Timotius, K. H. (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
Orange II is the most used colorant in industries which involve coloring process. So far, Orange II decolorization process by Enterococcus faecalis ID 6017 under batch system has been proven to be able to decolorize orange to colourless. In the presence of intermediates accumulation in batch system, claimed bioprocess development with continues system. An hypothesis was carried out that continues system could reduce intermediates generated by Orange II degradation. This research aimed to know the growth of Enterococcus faecalis and its Orange II decolorization ability in the medium supplemented with Orange II with different concentration under continues system. The research was set on continues system with single cultures Enterococcus faecalis, grown in medium with 80, 120, or 160 mg/L Orange II concentration. Measured parameters were Orange II concentration, biomass, glucose concentration, intermediates compound (sulphanilic acid). It could be concluded that under continues system (D = 0.06 hour-1), Enterococcus faecalis could decolorize Orange II until 160 mg/l.